REPRODUCTIVE HEALTH SOCIALIZATION FOR ADOLESCENTS USING A COMBINATION OF CROSSWORDS AND LECTURE METHODS - Natasha Vine Angelique; Afifur Rafi Hilmi Aziz; Asvarina Al Jannati; Alvin Virya; Salsabela Komalasari; Prima Kartika; Rr Mitsaqon Gholiza Fudryasah; Hisaanti Farayi Yunenda; Sjahfryza Ahmad Ma'arif (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
The human reproductive system begins to become active at the age of adolescence. Therefore, they are expected to understand how to maintain the cleanliness and health of their reproductive organs to reduce the risk of unwanted pregnancy and the transmission of HIV/AIDS. With this urgency, the following activities were carried out to provide education about reproductive health to adolescents in Sekaran Village, Balen District, Bojonegoro Regency. This activity was carried out to 47 students in grades 7, 8, and 9 of MTs Manba'ul Huda, Bojonegoro Regency. The activities were chosen using the methods of lecture and playing crossword, as the presence of games can enhance students' interest in engaging with the presented material. The data was collected using a questionnaire in the form of pre-test and post-test given to the students. Then statistical analysis was performed using the Wilcoxon test to measure the difference between the pre-test and post-test scores. From these two values, it was found that there was an average increase from the results of the pre-test (32.34 Â± 20.664) to the post-test (58.30 Â± 26.826). From the results of data analysis that has been carried out, it can be concluded that the method of playing crossword and lecture is effective for increasing the knowledge of MTs Manba'ul Huda students about adolescent reproductive health.